2021
DOI: 10.1016/j.psj.2021.01.027
|View full text |Cite|
|
Sign up to set email alerts
|

Research Note: Molecular surveillance of Avian Paramyxovirus type-1 in nonvaccinated village chickens in Central Rift Valley of Oromia, Ethiopia

Abstract: Newcastle disease ( ND ) is a major infectious disease of poultry caused by a virulent strain of Avian Paramyxovirus type-1 ( APMV-1 ). It is a major threat to the poultry industry in many countries of the world including Ethiopia. The aim of this study was to conduct molecular surveillance of ND Virus and identify potential risk factors for nonvaccinated village chicken in Central Rift Valley of Oromia, Ethiopia. A total of 84 pooled swab samples, each made from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
2
1
1
Order By: Relevance
“…The detection rate of NDV strain from pooled swab samples was 7.69%, which is different from the previous reports by Milkesa et al 17 and Gelana 16 with 15.47% and 16.7%, respectively, in the Mid-Rift Valley area. There was a statistically significant difference between the different swab types (tracheal swab and cloacal swab samples) in the occurrence of NDV strain (p<0.05) where higher detection rate was recorded from tracheal swabs.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The detection rate of NDV strain from pooled swab samples was 7.69%, which is different from the previous reports by Milkesa et al 17 and Gelana 16 with 15.47% and 16.7%, respectively, in the Mid-Rift Valley area. There was a statistically significant difference between the different swab types (tracheal swab and cloacal swab samples) in the occurrence of NDV strain (p<0.05) where higher detection rate was recorded from tracheal swabs.…”
Section: Discussioncontrasting
confidence: 92%
“…Our study also revealed a 10.75% and 22.2% detection rate of NDV strain in Mid-Rift Valley and central part of Ethiopia, respectively. The result of the current study in Rift Valley is comparable with previous reports of 12.7% and 11.6% by Gelana 16 and Terefe et al, 8 respectively; however, it is relatively lower (15.47%) than the report of Milkesa et al 17 The result of the study in the central part of Ethiopia did not agree with the findings of Miressa et al, 18 26.7% in Adama and Bishoftu; and Gelana, 16 40%, in Bishoftu. This difference might be due to the difference in the study population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In recent years, researchers have been implementing molecular techniques to develop new tools to assist scientists in epidemiological and ecological studies to control the common foodborne bacteria linked to poultry products associated with human gastroenteritis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. To this end, impressive progress has been made in next-generation sequencing (NGS), which has allowed for a more comprehensive characterisation of microbiota ecology in poultry [ 16 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%